Research progress of ginseng in the treatment of gastrointestinal cancers - Baoyi Ni; Xiaotong Song; Bolun Shi; Jia Wang; Qianhui Sun; Xinmiao Wang; Manman Xu; Luchang Cao; Guanghui Zhu; Jie Li (Frontiers Media S.A., 2022)
Cancer has become one of the major causes of human death. Several anticancer drugs are available; howeve their use and efficacy are limited by the toxic side effects and drug resistance caused by their continuous application. Many natural products have antitumor effects with low toxicity and fewer adverse effects. Moreover, they play an important role in enhancing the cytotoxicity of chemotherapeutic agents, reducing toxic side effects, and reversing chemoresistance. Consequently, natural drugs are being applied as potential therapeutic options in the field of antitumor treatment. As natural medicinal plants, some components of ginseng have been shown to have excellent efficacy and a good safety profile for cancer treatment. The pharmacological activities and possible mechanisms of action of ginseng have been identified. Its broad range of pharmacological activities includes antitumor, antibacterial, anti-inflammatory, antioxidant, anti-stress, anti-fibrotic, central nervous system modulating, cardioprotective, and immune-enhancing effects. Numerous studies have also shown that throuth multiple pathways, ginseng and its active ingredients exert antitumor effects on gastrointestinal (GI) tract tumors, such as esophageal, gastric, colorectal, liver, and pancreatic cancers. Herein, we introduced the main components of ginseng, including ginsenosides, polysaccharides, and sterols, etc., and reviewed the mechanism of action and research progress of ginseng in the treatment of various GI tumors. Futhermore, the pathways of action of the main components of ginseng are discussed in depth to promote the clinical development and application of ginseng in the field of anti-GI tumors.